Their ancient glittering eyes : remembering poets and more poets : Robert Frost, Dylan Thomas, T.S. Eliot, Archibald MacLeish, Yvor Winters, Marianne Moore, Ezra Pound - Hall, Donald, 1928-; Hall, Donald, 1928- (New York : Ticknor & Fields, 1992)
Includes portraits of the poets Robert Frost, Dylan Thomas, T.S. Eliot, Marianne Moore, Archibald MacLeish, Yvor Winters, Marianne Moore, and Ezra Pound.
Vanity, fame, love, and Robert Frost -- Dylan Thomas and public suicide -- Notes on T.S. Eliot -- Rocks and whirlpools: Archibald MacLeish and Yvor Winters -- Marianne Moore valiant and alien -- Fragments of Ezra Pound.
Rev. and enl. ed. of: Remembering poets. c1978.
Includes index.
Also issued online.
Keywords: Hall, Donald, -- 1928- -- Friends and associates; Poets, American -- 20th century -- Interviews; Poets, American -- 20th century -- Biography; Poetry -- Authorship; Poetics -- History -- 20th century